Effect of Stroke Length and Weight of Waste Valve on the Performance of Hydraulic Ram - Suseela, P; George, T P (Journal of Agricultural Engineering, 2003)
A hydraulic ram (5 cm x 2.5 cm) was designed, fabricated and installed at KCAET, Kerala Agricultural University, Tavanur. Fabrication of ram was done using locally available pipes and fittings and with some components which could be easily made. Test was conducted to study the effect of stroke length and weight of waste valve on the performance of hydraulic ram. It was found that delivery discharge and efficiency of hydraulic ram were found to increase with decrease in the stroke length of waste valve for a given delivery head. The study also revealed that there was a minimum weight of waste valve corresponding to a particular weight of delivery valve at which the hydraulic ram functioned satisfactorily. Hydraulic ram with heavier waste valve was found to operate at wider range of hydraulic head. Delivery discharge corresponding to a particular delivery head was found to increase with increase in weight of waste valve.